2011
DOI: 10.1158/1078-0432.ccr-10-3377
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Expression Analysis of MET, MACC1, and HGF in Metastatic Colorectal Cancer: Response to Met Inhibition in Patient Xenografts and Pathologic Correlations

Abstract: Purpose: We determined the gene copy numbers for MET, for its transcriptional activator MACC1 and for its ligand hepatocyte growth factor (HGF) in liver metastases from colorectal carcinoma (mCRC). We correlated copy numbers with mRNA levels and explored whether gain and/or overexpression of MET and MACC1 predict response to anti-Met therapies. Finally, we assessed whether their genomic or transcriptional deregulation correlates with pathologic and molecular parameters of aggressive disease.Experimental Design… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 31 publications
(34 reference statements)
1
100
0
3
Order By: Relevance
“…64 However, the data reported on MET gene copy number are in disagreement with previous studies showing that MET amplification is a rare event in primary colorectal cancer tumors. 65,66 This discrepancy may be due to methodological differences as we used a quantitative RT-PCR assay instead of FISH and thus the reported increase in MET gene copy number could be due to a polysomy of chromosome 7 and not locus specific amplification of MET. Moreover, the choice of TOP3A as a reference gene in our experiments, which resides on chromosome 17 whose loss has been associated with transition to carcinoma, may be another reason for this discrepancy; however this possibility was investigated using KRAS as a reference gene and similar results were obtained (unpublished results).…”
Section: Discussionmentioning
confidence: 97%
“…64 However, the data reported on MET gene copy number are in disagreement with previous studies showing that MET amplification is a rare event in primary colorectal cancer tumors. 65,66 This discrepancy may be due to methodological differences as we used a quantitative RT-PCR assay instead of FISH and thus the reported increase in MET gene copy number could be due to a polysomy of chromosome 7 and not locus specific amplification of MET. Moreover, the choice of TOP3A as a reference gene in our experiments, which resides on chromosome 17 whose loss has been associated with transition to carcinoma, may be another reason for this discrepancy; however this possibility was investigated using KRAS as a reference gene and similar results were obtained (unpublished results).…”
Section: Discussionmentioning
confidence: 97%
“…Metastasis-associated in colon cancer-1 (MACC1) has been reported to promote tumor proliferation and invasion mediated via hepatocyte growth factor (HGF)/ mesenchymal-epithelial transition factor (c-Met) signaling in colorectal cancer (Stein et al, 2009;Galimi et al, 2011;Migliore et al, 2012). Recently, a clinical study showed that aberrant overexpression of MACC1 may indicate poor prognosis of ovarian cancer patients for early recurrence and distance metastasis (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MACC1 kolorektal karsinomada tanı koydurucu bir belirteçtir (11). Ayrıca bazı çalışmalar mide (12), akciğer kanseri (13,14), hepatosellüler karsinoma (15), yumurtalık kanseri (17) ve pankreatik kanser (18) metastazında yüksek düzeyde MACC1 mRNA varlığını göstermiştir.…”
Section: Discussionunclassified
“…Çünkü MACC1, birincil kolon kanserine göre yayılımcı kolon kanserinde aşırı ifade olur (5,6,(8)(9)(10). Benzer şekilde, normal dokulara göre birincil kolon kanserinde de aşırı ifade olur (9,11). Bu da, MACC1 mRNA aşırı ifadesinin mide (12), akciğer (13,14), hepatosellüler (15,16), yumurtalık (17) ve pankreatik kanser (18) gibi diğer katı tümörler için sağkalımı ve kanser ilerleyişi için bir biyobelirteç olarak görülebileceğini düşündürmektedir.…”
Section: Introductionunclassified